Additions to clay bodies - Standen, Kathleen (London Bloomsbury, 2013)
"Beginning with an introduction to collecting local clay and making your own clay bodies, the book moves on to cover the array of additions being used by artists today, from hard materials like stones, glass and rust, to combustible matter and fibre, metals including wire and mesh, and colour in various forms."--Back cover.
Includes bibliographical references (page 126) and index.
Keywords: Ceramic sculpture -- Technique; Ceramic sculpture -- 21st century